Development of Wordwall Educative Games Applications as Learning Media For Understanding PJOK Materials For Elementary Students - Saputri, Sukartini Nani; Drajati, Nur Arifah; Sukmawati, Fatma (Universitas Sebelas Maret, 2023)
This article discusses the design and product development of PJOK learning media in elementary schools in the form of wordwall educational game applications and to determine the effectiveness of using wordwalls in PJOK learning as measured by students' understanding of PJOK material using wordwalls. The research was conducted to support teacher competency in Technological Pedagogical Content Knowledge (TPACK) abilities. The research approach used is a mixed method with a 4-D development model design, namely define, design, develop, and disseminate. Data obtained by means of questionnaires, documentation, and interviews. The results of the study were 1) wordwall product designs were made based on an analysis of teacher needs for learning media in elementary schools and based on curriculum analysis in the form of Basic Competency analysis and its compatibility with the characteristics of grade 2 elementary school students, 2) the resulting product from the research was wordwall educational games in 4 types of games, namely maze chase, airplane, balloon pop, and open the box, and students' ability to understand PJOK material very well through the help of wordwall games. Based on the research results, the wordwall application can be recommended for further development in other Basic Competencies accompanied by learning videos.